2017
DOI: 10.1108/jmp-08-2016-0264
|View full text |Cite
|
Sign up to set email alerts
|

General performance factors and group differences in assessment center ratings

Abstract: Purpose-The purpose of this paper is to establish the extent of general performance factors (GPF) in assessment center (AC) exercises and dimensions. The study further aims to determine if larger GPF contributes to larger ethnic group differences across exercises and dimensions that are more cognitively loaded in an emerging market context. Design/methodology/approach-The authors analyzed data across three independent AC samples (Sample 1: N = 172; Sample 2: N = 281; Sample 3: N = 428). The Schmid-Leiman solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Assessors make observations and judgments of behaviors relevant to dimensions as elicited by exercises. Research has demonstrated the differing nature of dimensions and simulation exercises, the role of cognitive ability in performance effectiveness, and racial subgroup differences (Bobko & Roth, ; Buckett, Becker, & Roodt, ; Ployhart & Holtz, ; Roth, Bobko, McFarland, & Buster, ). This raises the question of whether assessor errors occur in different ways in different dimensions and different exercises, and whether they are influenced by assessor and assesse demographic variables.…”
Section: Rater Error As a Mechanism Driving Subgroup Differencesmentioning
confidence: 99%
“…Assessors make observations and judgments of behaviors relevant to dimensions as elicited by exercises. Research has demonstrated the differing nature of dimensions and simulation exercises, the role of cognitive ability in performance effectiveness, and racial subgroup differences (Bobko & Roth, ; Buckett, Becker, & Roodt, ; Ployhart & Holtz, ; Roth, Bobko, McFarland, & Buster, ). This raises the question of whether assessor errors occur in different ways in different dimensions and different exercises, and whether they are influenced by assessor and assesse demographic variables.…”
Section: Rater Error As a Mechanism Driving Subgroup Differencesmentioning
confidence: 99%
“…Bias, prejudice and unfairness in the use of ACs could result from many variables such as the attitudes, values and judgements of the assessor (Kuncel & Highhouse, 2011;Muchinsky et al, 2005), properties of the measures (Buckett, Becker & Roodt, 2017;Foxcroft & Roodt, 2013;Moerdyk, 2009), contextual realities embodied in the socio-political world at the time (Donald et al, 2014;Foxcroft & Roodt, 2013), cultural preferences for certain personality characteristics such as bias towards extroverts (Collins et al, 2003;Crawley, Pinder & Herriot, 1990;De Beer, 2012;Furnham, Jensen & Crump, 2008;Jackson et al, 2010) and a tendency towards cloning (Bagues & Perez-Villadoniga, 2013;Fiske, 1999). In ACs specifically, preconceived ideas, different points of view, different interpretations and differences in scoring and scoring methods, especially where judgement is concerned, may lead to disparate outcomes (Kuncel, Klieger, http://www.sajip.co.za Open Access…”
Section: Bias and Prejudicementioning
confidence: 99%